Social Media Marketing and Consumer Behaviour: Reflection and Future Perspectives - Saud, Hari Singh; Kumar, Rajender; Rawat, Babu Ram; Kumari, Madhu; Masuma, Arjuman (KMC Journal, 2025)
This study presents a comprehensive bibliometric and thematic analysis of digital marketing and consumer behaviour research from 2010 to 2024, examining publication trends, citation impacts, key contributors, and evolving research themes. Data were extracted from the Scopus and Web of Science databases. In total, 1803 research journals were analyzed. This study utilized R programming software (R Studio) to analyze the bibliometric data. The analysis highlights a rapidly expanding field centered on social media marketing and consumer behaviour. The findings reveal an exponential growth in annual publications, increasing from 11 articles in 2010 to 284 in 2023, with a notable 16.01% yearly growth rate, signaling the field’s expanding scholarly significance. However, the trend appears to decrease in 2024, as data extracted in the first quarter suggests a decline. Three key field plots structure the discussion and dominant themes: platform-specific studies (Instagram, Facebook), brand equity, and ROI measurement. Thematic trends further underscore the shift from theoretical frameworks to data-driven applications, with emerging focus areas such as adolescent consumer behaviour and cross-cultural dynamics. The study concludes that while social media marketing research has matured rapidly, challenges remain in striking a balance between productivity and its impact. Future research should address understudied platforms (e.g., TikTok), integrate advanced analytics, and reconcile new digital behaviours with classic marketing theories. This analysis provides a roadmap for scholars and practitioners to navigate the evolution of the field and prioritize high-impact research avenues.